A multi-modality medical imaging head and neck phantom: Part 1. Design and fabrication. (April 2022) - Deene, Yves De; Wheatley, Morgan; Greig, Thomas; Hayes, Daniel; Ryder, William; Loh, Han
Graphical abstract: Highlights: Multi-modality medical imaging Head & Neck phantom for quality assurance, experimental testing and training. Realistic vasculature and micro-vasculature hardware and software model for flow imaging and perfusion scanning. Physiologically realistic pressure-flow dynamics. Tissue equivalent structures. Demonstration for MRI, X-ray CT, Doppler Ultrasound and Nuclear Medicine. Abstract: A novel anthropomorphic head and neck phantom which features the emulation of blood flow and perfusion is proposed. The phantom is helpful in both education and research and contains major blood vessels and a porous silicone elastomer brain compartment with microvascular capillary flow. The porous brain compartment is fabricated by use of a novel cast-moulding-dissolution technique. The skull and vertebra are fabricated by a combination of 3D printing and cast-moulding and are tissue equivalent with CT numbers ranging from 1000 HU to 1200 HU. The elastic structure of the phantom allows ultrasound imaging in the neck region. MRI compatible pressure sensors measure the pressure in the carotic arteries and the jugular veins and pulsatile flow is created by use of a peristaltic pump. The pressure-flow dynamics are physiologically realistic and also matches well with computational simulations of porous Darcy flow. The phantom can be used to optimize and validate MRI pulse sequences and protocols for flow imaging, MR angiography, Arterial Spin Labeling (ASL) and dynamic contrast enhanced (DCE) MRI.